Pengaruh Electronic Word of Mouth, Kualitas Produk dan Product Knowledge Terhadap Keputusan Pembelian Produk Kosmetik BLP Beauty (Studi Pada Mahasiswi Di Kota Mataram) - Salsabhilla Dhea Febyana; Lalu Edy Herman Mulyono; Muhammad Mujahid Dakwah (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
This research examines the effect of electronic word of mouth, product quality and product knowledge on purchasing decisions for BLP Beauty cosmetic products in Mataram City. The population in this research were female students in Mataram City who had and are currently using BLP Beauty cosmetic products. The data used is primary data obtained from 70 sample respondents. The sampling technique is through a non-probability sampling technique with a purposive sampling method. The analysis used is multiple regression analysis. The data analysis technique uses the SPSS version 25 program. Based on the results of statistical data analysis, the indicators in this research are valid where in the classical assumption test, the data is normally distributed and there is no multicollinearity. The results of this research indicate that electronic word of mouth and product knowledge partially have a significant effect on purchasing decisions. While product quality has no significant effect on purchasing decisions.